Pengaruh Motivasi dan Displin Kerja Serta Gaya Kepemimpinan Terhadap Kinerja Kepolisian di Polres Banyuasin - Omar Hendro; Mei Priyanto; Mustopa Marlibatubara (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
Riset with the title Effect of Work Motivation and Discipline and Leadership Style on Police Performance in Banyuasin Regional Police. The purpose of this study answers the problem formulation, which is first to analyze the effect of motivation, discipline and leadership style together (simultaneously) on the performance of the police in the Banyuasin Regional Police. Second, analyze the effect of motivation on police performance. Third, analyze the effect of discipline on police performance. Fourth, analyze the influence of leadership style on police performance. The design of this study is an associative type of research, which is to find out the relationship between two variables X (motivation, discipline, and leadership style) and Y (performance). The population of 462 people, with a sample of 82 respondents Banyuasin Police Personnel with an error rate of 10%. The F Test result states that there is a significant relationship between Motivational Variables (X1), Work Discipline (X2), and Leadership Style (X3), on the Bound Variable, namely Police Performance (Y). T-test results of the three independent variables have a Sig coefficient value, namely that there is a significant relationship between Motivational Variables (X1), Work Discipline (X2), and Leadership Style (X3), on the Bound Variable, namely Police Performance (Y1). The results of the multiple regression equation Y = 0.503 + 0.190X1 + 0.188X2 + 0.440X3. The three coefficients of the free variable are positive, this shows a positive linear direction (unidirectional) between Motivational Variables (X1), Work Discipline (X2), and Leadership Style (X3), on the Bound Variable, namely Police Performance (Y). This study concludes first, work motivation, work discipline, and leadership style together have a significant effect on the performance of the Banyuasin Regional Police. Second, work motivation, work discipline, and leadership style partially have a significant effect on performance. Third, the leadership style contributed greatly to the Banyuasin Police Performance, while the lowest was the Work discipline towards the Banyuasin Police Performance (Y).